Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1750-3639.2011.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Murine Bioassay to Resolve Ovine Transmissible Spongiform Encephalopathy Cases Showing a Bovine Spongiform Encephalopathy Molecular Profile

Abstract: Two cases of unusual transmissible spongiform encephalopathy (TSE) were diagnosed on the same farm in ARQ/ARQ PrP sheep showing attributes of both bovine spongiform encephalopathy (BSE) and scrapie. These cases, UK-1 and UK-2, were investigated further by transmissions to wild-type and ovine transgenic mice. Lesion profiles (LP) on primary isolation and subpassage, incubation period (IP) of disease, PrPSc immunohistochemical (IHC) deposition pattern and Western blot profiles were used to characterize the prion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 44 publications
5
33
0
Order By: Relevance
“…In accordance with this hypothesis we have previously reported that PrP Sc deposition patterns indicative of specific strains were identified following first passage of ovine classical scrapie isolates to wild-type mice [10,18,19]. …”
Section: Introductionsupporting
confidence: 77%
“…In accordance with this hypothesis we have previously reported that PrP Sc deposition patterns indicative of specific strains were identified following first passage of ovine classical scrapie isolates to wild-type mice [10,18,19]. …”
Section: Introductionsupporting
confidence: 77%
“…Out of 10 inocula that were negative in RIII mice, only one became positive when assayed in TgshpXI mice (see Supplementary Table 1a for details). Although TgshpXI mice were inoculated with only 20 ml of inoculum IC and RIII mice were inoculated with 20 ml IC plus 100 ml IP, previous studies in transgenic mice showed no difference between the two inoculation regimes (Beck et al, 2012;Vickery et al, 2014). While PrP d /PrP res is widely considered as the best surrogate marker for TSE infections, its relationship with actual infectivity is not always clear, either in qualitative or quantitative terms.…”
Section: Discussionmentioning
confidence: 98%
“…There are some limitations, however, as it has been demonstrated by recent studies, according to which scrapie-infected sheep can produce a similar incubation period and lesion profile to BSE upon primary isolation in RIII mice [34,41]. It was still possible, however, to confirm these cases as scrapie using histopathology, Western blot and IHC although detailed description of the PrP Sc types in the mouse brain was not attempted.…”
Section: Introductionmentioning
confidence: 99%